2021
DOI: 10.3390/ma14143983
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of High Strength Silica Aerogel Composites via a Water Solvent System and Ambient Pressure Drying without Surface Modification or Solvent Replacement

Abstract: To further reduce the manufacturing cost and improve safety, silica aerogel composites (SAC) with low density and low thermal conductivity synthesized via ambient pressure drying (APD) technology have gradually become one of the most focused research areas. As a solvent, ethanol is flammable and needs to be replaced by other low surface tension solvents, which is dangerous and time-consuming. Therefore, the key steps of solvent replacement and surface modification in the APD process need to be simplified. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…[134] These types of composites can be prepared by dispersing fibers in the sol prior to gelation, followed by Figure 6. a) Schematic presentation of the synthesis of fiber-reinforced silica aerogels, [138] b) stress-strain profile for mullite fiber-reinforced silica aerogels, [140] c) effect of fiber density on the mechanical properties of silica aerogels, [138] d) process for the synthesis of polymer reinforced silica aerogels and representative set of monomers used, [141] and e) effect of PVP wt% on the Young's modulus of bending of silica aerogels. [142] a-c) Adapted with permission.…”
Section: Aerogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[134] These types of composites can be prepared by dispersing fibers in the sol prior to gelation, followed by Figure 6. a) Schematic presentation of the synthesis of fiber-reinforced silica aerogels, [138] b) stress-strain profile for mullite fiber-reinforced silica aerogels, [140] c) effect of fiber density on the mechanical properties of silica aerogels, [138] d) process for the synthesis of polymer reinforced silica aerogels and representative set of monomers used, [141] and e) effect of PVP wt% on the Young's modulus of bending of silica aerogels. [142] a-c) Adapted with permission.…”
Section: Aerogelsmentioning
confidence: 99%
“…b) Adapted under the terms of the CC‐BY Creative Commons Attribution 4.0 International license ( https://creativecommons.org/licenses/by/4.0). [ 140 ] Copyright 2021, The Authors, published by MDPI. d) Adapted with permission.…”
Section: Development Of Mechanically Strengthened Aerogels: Tradition...mentioning
confidence: 99%
“…al, Fiber density's influence on SAC's thermal conductivity, mechanical qualities, and other physical characteristics is explored in depth. The findings reveal that at 10% strain, the compressive strength of SAC is 1.348 MPa and the thermal conductivity at 1100 °C is 0.127 W/m K. SAC is anticipated to be employed as a useful and costeffective insulating material because of its easy synthesis method and high thermal-mechanical performance [19]. J. Ben Naceur et al, analysis, structural and optical characteristics of sol-gelthey found processed TiO2 thin films doped with iron ions (Fe3+).…”
Section: Introductionmentioning
confidence: 99%
“…These materials reach thermal conductivities around 10–20 mW/mK and have a wide variety of applications [ 9 , 13 ]. Nevertheless, their long and multi-step synthesis process, high production costs, poor mechanical properties and health issues (i.e., irritant to the eyes, skin, respiratory tract, and digestive system) limit their practical applications and mass production [ 1 , 6 , 16 , 17 , 18 ]. Another type of aerogels that have also attracted attention are those based on resorcinol–formaldehyde (RF).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal conductivities of 26 and 38 mW/mK were achieved for silica and hybrid xerogels, respectively. The use of MTMS improve the mechanical resistance of the xerogels avoided shrinkage during drying, but did not favor the insulating performance [ 18 , 23 ]. Thus, new strategies focusing on the role of chemical and porous properties should be adopted to optimize the insulating performance of hybrid xerogels.…”
Section: Introductionmentioning
confidence: 99%